Normalizing Alternatives with Frequently Asked White Questions - Tattrie, Hailie; Rehberg Sedo, DeNel (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2025)
This article is the result of a case study of Frequently Asked White Questions (FAWQ) by Ajay Parasram and Alex Khasnabish. We examine FAWQ as a tool for fostering meaningful conversations about race and anti‑racism. In order to facilitate social change through books and book talk, a book must be discoverable and visible. Further, for a book to have this kind of social impact, we argue that three things must be true: that the guiding ethos of the publisher is one of progressive politics; that the author(s)’ stories are authentic and accessible; and that communication about the book’s contents between the publishing agents, authors, and readers follows a politic of love. Situating this discussion within the current political environment, we highlight the urgency of such conversations. Drawing from Paulo Freire’s concept of dialogue as foundational to social transformation, we argue that by normalizing discomfort and centering relational engagement, the book offers a model for navigating difficult discussions in ways that resist ideological rigidity and promote sustained, everyday activism.